Adolescent athlete’s knowledge, attitude and practices about menstrual hygiene management (MHM) in BKSP, Bangladesh (Asian Journal of Medical and Biological Research, 2019)
Maintaining proper hygiene during menstruation prevents certain reproductive illnesses. For female athletes, they need to put an extra effort to keep themselves healthy at this time because of their daily strenuous activities. In this study, we assessed the level of knowledge, attitude and practices about menstrual hygiene management among adolescent trainee athletes. A cross-sectional study was carried out among adolescent trainee athletes from BKSP. Samples were chosen conveniently from different sports departments. In total, 143 Female athletes who regularly menstruate were included. A semi-structured questionnaire was used to determine the level of knowledge, attitude and practices and their associated factors. One-way analysis of variance (ANOVA) was used to compare means of outcome variables. The mean ± SD age of our participant was 14.31 ± 1.48. Majority of the participants were scared during their first menstruation (39.9%). Mothers were the main source of information (84.6%). Majority of the participants had poor knowledge (56.6%) and practices (68.5%) while the level of attitude was good (67.1) regarding menstruation. Age-group was associated with knowledge score (p=0.034) regarding menstruation while family income was associated with attitude (p=0.014). Educational level of father was associated with both knowledge (p=0.049) and attitude (p=0.010). Poor level of knowledge and practices were observed among the survey respondents, though the level of attitude was satisfactory. Mothers were the primary source of information regarding menstrual hygiene. It is important to provide menstrual hygiene education to the young athletes from a reliable and formal source.Asian J. Med. Biol. Res. June 2019, 5(2): 126-137